2006
DOI: 10.1159/000093664
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Causes of Seizures at the Time of Diagnosis of Probable Alzheimer’s Disease

Abstract: Background/Aims: To investigate the frequency of epilepsy at the time of diagnosis of Alzheimer’s disease (AD). Methods: Observational study, Cognitive Function Clinic population, over a 6-year period (2000–2005 inclusive). Results: In a cohort of 177 patients with newly diagnosed clinically probable AD, 12 (6.8%) had a history of seizure disorder and/or were using anti-epileptic medications at the time of diagnosis. In 6 of these cases (3.4%), seizure onset was approximately concurrent with the onset of cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 51 publications
5
78
0
5
Order By: Relevance
“…Nutritional education programmes for caregivers of patients with AD may help to resolve this problem [27] . We also found that epilepsy was more commonly diagnosed in AD, and a previous study, which reported that 6.8% of their AD patients had a history of epilepsy, supports this observation [28] .…”
Section: Discussionsupporting
confidence: 89%
“…Nutritional education programmes for caregivers of patients with AD may help to resolve this problem [27] . We also found that epilepsy was more commonly diagnosed in AD, and a previous study, which reported that 6.8% of their AD patients had a history of epilepsy, supports this observation [28] .…”
Section: Discussionsupporting
confidence: 89%
“…Prevalence of unprovoked seizures in Alzheimer's disease (AD) is significantly higher than in age-matched control populations (Hauser et al, 1986;Mendez et al, 1994;Hesdorffer et al, 1996;Amatniek et al, 2006;Lozsadi and Larner, 2006). The risk of epileptic seizures is particularly high in AD patients with earlyonset dementia and during early stages of the disease, reaching an 87-fold increase in seizure incidence compared with an agematched reference population (Amatniek et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such provision may be required because insufficient neurological expertise is deemed available in dedicated learning disability clinics. The correct diagnosis of late-onset seizures in Down syndrome is crucial since this may herald onset of cognitive decline [11,12] , in the same way that seizure onset concurrent with the development of Alzheimer's disease has been documented in the non-Down syndrome population [13] , and hence be a marker for consideration of anti-dementia drug therapy. Such medications have been investigated in Down syndrome [4] , and although their exact place in management remains to be defined, it would seem likely that their greatest benefit will be in early cognitive decline.…”
Section: Discussionmentioning
confidence: 99%